Integrated control of fungal pathogens causing agent of crown and root rot disease on potato in middle of iraq - Alhamiri, Yaser N. H. (Journal of Kerbala for Agricultural Sciences, 2016)
The aim of this study was to evaluate of some agents of integrated control such as Saccharomyces cervisiae , Bacillus thuringiensis , plant extracts (Eucalyptus and Stachys) and Beltanol to control the potato root rot disease caused by Fusarium solani and Rhizoctonia solani. which were isolated from the infected roots of potato plants . One isolate of each species , that proved pathogenic in previous test was used. Laboratory results showed that biocontrol agent S. cervisiae and B.thuringiensis had a high antagonistic activity against F.solani and R.solani inhibition 88-67% of pathogenic fungs growth on potato dextrose agar (PDA) . plant extracts (Eucalyptus and Stachys ) showed high percentage of growth reduction reached 100-80 % to F.solani and R.solani when plant extracts was used at rate of 20 mg/l in potato dextrose agar . Results of the efficacy of fungicides indicated that Beltanol were superior in inhibition growth of the pathogenic fungi and average of effective concentration were 1 ml/l . Results of several treatments to control F.solani and R.solani in pots under green house conditions, showed that treatments with S. cervisiae, B.thuringiensis , plant extracts ( Eucalyptus and Stachys ) and Beltanol treatment of achieved the high control for F.solani and R.solani , Field results indicated that all treatments reduced disease severity caused by F.solani significantly compared to untreated plots 50% , 25% , 16% , 62% , 0.0% respectively . and R.solani treatments 41% , 16% , 32% , 62% , 0.0% respectively . while Results of treatments to control (F.solani + R.solani) 50% , 28% , 38% , 62% , 0.0% respectively ., Furthermore the dry shoot , root weights and plant height increased. Treatments of (S. cervisiae + B.thuringiensis) showed lower disease severity (9.23%) and higher dry weights of shoot , root and plant height compared with treatment of plant extracts (Eucalyptus + Stachys ) (25%) to both fungi . while Results of treatment (F.solani + R.solani) disease severity 13.46% , 32%. Respectively. Integrated control treatment whithout fungicide (S. cervisiae + B.thuringiensis + plant extracts Eucalyptus + Stachys) achieved the highest degree of control for F.solani , R.solani and (F.solani + R.solani) (0.0%).